I(a)mmoral understanding Pentecostal church leaders' reception of Vice Ganda's homosexual acts in Showtime - Rivera, Maria Christina Angelica Talinio 1990-; Austria, Fernando A., Jr. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2011)
"What will happen if an aberration to the dominant ideology in society suddenly emerges and confuses the audiences' reading of a media text? This study aims to answer this question by analyzing the reactions of Pentecostal church leaders towards Vice Ganda's expressions of himself in Showtime. Using Stuart Hall's Encoding Decoding theory as framework, the researcher studied the hegemonic ideologies in media and the church that served as the dominant codes in the communicative process where media is the encoder of messages and the Pentecostal pastors are the decoders. Vice Ganda on the other hand emerges as the aberration to the dominant Patriarchal ideology in society. The researcher's findings would show how Vice Ganda entertained, impressed and at the same time offended and threatened the Pentecostal pastors as he broke the Filipinos' stereotypes of gays on TV."
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman